2020
DOI: 10.1098/rsif.2020.0568
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stimuli and matrix properties modulate cancer spheroid growth in three-dimensional gelatin culture

Abstract: Most patients who succumb to cancer have metastases to bone that contribute to their death. Cancer cells that metastasize to bone are regularly subjected to mechanical stimuli that may affect their proliferation, growth and protein expression. Understanding why some cancer cells thrive in this environment could provide insight into new approaches to prevent or treat metastasis to bone. We used 4T1 cells as a model of breast cancer cells, and implanted them in gelatin hydrogels with moduli of 1 or 2.7 kPa to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…ionic composition [ 16 18 ]) and physical properties (e.g. matrix stiffness [ 19 21 ]) of the tumour [ 22 , 23 ].…”
Section: What Cancer Patients and Mathematical Models Tell Us About T...mentioning
confidence: 99%
“…ionic composition [ 16 18 ]) and physical properties (e.g. matrix stiffness [ 19 21 ]) of the tumour [ 22 , 23 ].…”
Section: What Cancer Patients and Mathematical Models Tell Us About T...mentioning
confidence: 99%
“…, 2015 ). In 3D culture models, the properties of the surrounding matrix also alter the size and the protein expression of spheroids formed by 4T1 cancer cells ( Curtis et al. , 2020b ).…”
Section: Resultsmentioning
confidence: 99%
“…Computational models have shown that these stiffness mismatches between cell types result in protection of smaller cells from mechanical stress during bone loading (Vaughan et al, 2015). In 3-D culture models, the properties of the surrounding matrix also alters the size and the protein expression of spheroids formed by 4T1 cancer cells (Curtis et al, 2020b).…”
Section: Cell Migration Toward Human Bone In 3-d Co-culturementioning
confidence: 99%
“…The microenvironment is soft with rigid struts of bone matrix. These changes of stiffness and mechanical stimulation were simulated in vitro by Curtis et al on a breast cancer cell line, 4T1, laden in a gelatin scaffold and showed changes in the proliferation and protein expression (PTHrP and OPN) within soft materials with mechanical properties similar to bone marrow [56]. This showed evidence of mechanosensitivity of cancerous cells to their microenvironment.…”
Section: Bone Metastasismentioning
confidence: 93%